A enunciação e a reflexividade no cinema documentário aproximaçoes teóricas, filmográficas e uma realização - BARBOSA, Douglas da Silva (2010)
This dissertation deals with the idea of enunciation in documentary cinema, also taking into account an aspect found within this field called reflexivity. Generally the questions of enunciation in the field of this cinema permeate the documentary undertaking from the film project to the moment of reception by the public who watch the film. In choosing this object of study it was aimed to find instigating aspects about the course of the documentary as an audiovisual product linked to the idea of enunciation about the lived world. The research joins together theoretical contributions of some authors around what we might consider typical of enunciation in documentary cinema, among them Fernão Ramos and Jean Louis Comolli, passing through the tendencies in this cinema and important film-makers with their films (among these: Eduardo Coutinho, 2005: O fim e o princípio ; João Moreira Salles, 2006 Santiago and Kiko Goifman, 2002: 33 ). Further on, a revealing discussion is made about the undertaking of the documentary Os Corrêa da Silva e Santos Reis (a short-film, 24 , the result of 12 hours of filming of raw material in the rural community of Água Limpa and with ex-inhabitants of that community). The results obtained with this dissertation point, generally, towards the notion of taking the câmera-image as a dimension of documentary enunciation which strengthens the persepective of enunciation about the lived world. At the end there is an understanding of a proposal of performance of the documentary film-maker which turns to the people, subjects of his/her action, in aiming to divide with them a cinematographic mise-en-scène capable of making emerge their singularity, as well as argumentation directed to something pre-defined. It is this aesthetic dependence on the real which strengthens a documentary film and allows one to see in it more than what is in its enunciation.